Desain Model Data Warehouse dengan Contoh Kasus Perguruan Tinggi - Spits Warnars (Universitas Bunda Mulia, 2017)
The growth high education has been raising the competition in high education market and Data Warehouse can be used as an effective technology weapon for going to battle in high education competition market. Data Warehouse can produce the reliable reports for high level management on high education in short time in order to make the faster and best decision making for not just only increasing number of students, but possibility to find mining fund which have never thinking before limited by high education ordinance. The reports which produce by Data Warehouse are made based on database which summarization transaction database can be trusted and far from manipulation, different with old producing reports based on transaction database which need to be questioned and need time to produce, need manipulation for the result, cannot be trusted and could be have different results if differentiate to other systems. Data Warehouse will be modeled with dimension business concept and be created based on hypercube which produced based on high demand reports which usually used by high level management. In every fact and dimension table will be inserted with fields which represent the construction merge loading as an ETL (Extraction, Transformation and Loading) extraction.Keywords: Data Warehouse, High Education, Hypercube, Business Dimensional Concept